2010
DOI: 10.4274/turkderm.44.102
|View full text |Cite
|
Sign up to set email alerts
|

The Coexistence of Coeliac Disease, Psoriasis and Vitiligo

Abstract: ÖzetÇölyak hastal›¤›n›n psoriasis ve vitiligo da dahil olmak üzere ço¤u otoimmun kökenli olan baz› hastal›klarla birlikteli¤i tan›mlan-m›flt›r. Burada palmoplantar pustular psoriasis tan›s› konulan ve özgeçmiflinde çölyak ve vitiligo hastal›¤› bulunan 26 yafl›nda bir kad›n olgu bildirilmektedir. Vitiligo, psoriasis ve çölyak hastal›¤› s›k görülen hastal›klar olup literatürde çölyak hastal›¤› ile birlikte olan vitiligo ya da psoriasis olgular› bildirilmifl olsa da, üçünün bir arada oldu¤u bir olguya rastlanmam›… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, the autoimmune mechanism characterized by T cell‐mediated hyperproliferation of keratinocytes has been implicated in the etiology. It has been reported that psoriasis may be associated with other autoimmune diseases 1 . Although psoriasis has been described as a skin disease, it is associated with many comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…However, the autoimmune mechanism characterized by T cell‐mediated hyperproliferation of keratinocytes has been implicated in the etiology. It has been reported that psoriasis may be associated with other autoimmune diseases 1 . Although psoriasis has been described as a skin disease, it is associated with many comorbidities.…”
Section: Introductionmentioning
confidence: 99%